Washington Irving. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut in Hildburghausen)
Muški portret.
Nepoznati autor.
Sredina ispod prikaza otisnuto: WASHINGTON IRVING // EIGENTHUM & VERLAG...
Digitalna reprodukcija
Keywords: Nadorezi; Portreti